2020
DOI: 10.1093/rheumatology/keaa720
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adiposity in patients with psoriatic arthritis and psoriasis alone and its relationship with metabolic and cardiovascular risk

Abstract: Background Fat mass distribution, especially in the abdominal visceral region, has been rarely evaluated in patients with PsA or psoriasis (PsO). Methods Patients with PsA and patients with PsO alone were evaluated and compared with control subjects (1:1 ratio in each patient group) matched for age, sex and BMI category. Body composition and fat distribution (android and visceral fat) were evaluated by DXA. Anthropometric mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 49 publications
0
16
1
Order By: Relevance
“…They found that patients with psoriasis are characterized by visceral fat accumulation, whereas the amount of fat in this region did not differ between PsA patients and controls. Furthermore, visceral adiposity in psoriasis correlated with CV risk measurements, such as SCORE (49).…”
Section: Fat Mass Distribution In Psoriatic Diseasementioning
confidence: 92%
“…They found that patients with psoriasis are characterized by visceral fat accumulation, whereas the amount of fat in this region did not differ between PsA patients and controls. Furthermore, visceral adiposity in psoriasis correlated with CV risk measurements, such as SCORE (49).…”
Section: Fat Mass Distribution In Psoriatic Diseasementioning
confidence: 92%
“…After testing for normality using the Kolmogorov-Smirnov test, the Mann-Whitney U Test for nonparametric data for independent samples was used, which revealed significant events, which have characteristically been associated with elevated BMI [4].…”
Section: Resultsmentioning
confidence: 99%
“…The following devices were used to derive body composition data for analysis in the 10 included BIA studies: BIA 101, Akern srl, Pontassieve, Florence, Italy [19]; single-frequency 50 kHz BIA 101 RJL, Akern Bioresearch, Florence [21, 22, 25, 32]; Bodystat 1500, Bodystat Ltd., Douglas, Isle of Man, UK [28], Tanita SC-330 Body Composition Analyzer, Tanita Corp., Tokyo, Japan [36], InBody 170, Biospace, South Korea [33]; Tanita TBF300, Tanita Corporation, Tokyo, Japan [34, 35].…”
Section: Resultsmentioning
confidence: 99%
“…The sample size was small (< 40) for a number of studies [26, 29, 31, 37]. Overall, four studies were regarded to be at high risk of bias [15, 18, 23, 26], two at medium risk of bias [26, 29] and 18 at low risk of bias [18, 20–23, 25, 28, 30, 31, 3341] using the ROBINS-I tool.…”
Section: Resultsmentioning
confidence: 99%